2021
DOI: 10.1016/j.jval.2020.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Disease Burden Attributable to the First Wave of COVID-19 in China and the Effect of Timing on the Cost-Effectiveness of Movement Restriction Policies

Abstract: Objectives Movement restriction policies (MRPs) are effective in preventing/delaying COVID-19 transmission but are associated with high societal cost. This study aims to estimate the health burden of the first wave of COVID-19 in China and the cost-effectiveness of early versus late implementation of MRPs to inform preparation for future waves. Methods The SEIR (susceptible, exposed, infectious, and recovered) modeling framework was adapted to simulate the health and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 18 publications
(28 reference statements)
2
71
0
2
Order By: Relevance
“…Mortality contributed (99.61%) towards almost all the DALYs due to the direct impact of COVID-19 in India, in line with other studies 49,54,57 . There was a median of 31.67 YLLs per COVID-19 death in India.…”
Section: Discussionsupporting
confidence: 89%
“…Mortality contributed (99.61%) towards almost all the DALYs due to the direct impact of COVID-19 in India, in line with other studies 49,54,57 . There was a median of 31.67 YLLs per COVID-19 death in India.…”
Section: Discussionsupporting
confidence: 89%
“…The CHEC quality assessment was performed for each included study (see Appendix 3 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2021.05.013 ). Nine studies scored high (>13/19), 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 10 studies scored moderate, 19 , 20 , 21 , 22 , 23 , 24 , 25 and 4 studies scored low (≤6/19). 26 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…A national lockdown has a moderate advantage in saving lives with tremendous costs and possible overwhelming economic effects. 8 Zhao et al 13 (China) General population Current practice: the real-world scenario in China, where the first movement restriction policies started on January 23, 2020 and ended on March 25, 2020 1-week delay in the imposition of movement restriction policies (MRPs) (MRPs end on the day when national newly confirmed cases reach zero) 2-week delay in the imposition of MRPs (MRPs end on the day when national newly confirmed cases reach zero) 4-week delay in the imposition of MRPs (MRPs end on the day when national newly confirmed cases reach zero) Extended SIRD—(S) susceptible, (Ip) presymptomatic, (Im) infectious with mild symptoms, (Ih) hospitalized, (R) recovered, and (D) deceased Net benefit (WTP = 70 892 RMB) Cost-benefit Period less than a year Societal and healthcare perspective Strategy A (“current practice”) dominates all other strategies, from both a healthcare perspective and societal perspective. At a WTP of 70 892 RMB per DALY averted, the probability that strategy A is more cost-effective compared with strategy B, C, and D is 96%, 99%, 100%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In 2020, epidemic suppression and/or mitigation have relied on non-pharmaceutical interventions (NPIs), including social distancing, school closure, mask use and case isolation. Although effective and widely adopted to limit severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and reduce COVID-19 burden, these interventions entail enormous economic costs and negatively affect quality of life 2 . Additionally, in many countries, relaxation of NPIs has led to a resurgence of the epidemic as herd immunity has not been reached thus far 3 .…”
Section: Mainmentioning
confidence: 99%